Land clearing, preparation and drone monitoring using red-green-blue (RGB) and thermal imagery for Smart Durian Orchard Management Project - Yusof, Ahmad Anas; Mohd Shaari Azyze, Nur Latif Azyze; Mohamed Nor, Mohd Khairi; Mohamed Kassim, Anuar; Shamsudin, Shamsul Anuar; Sulaiman, Hamdan; Hanafi, Mohd Aswad (Semarak Ilmu, 2021)
Malaysia's agricultural activity is progressing toward the use of precision agriculture and Internet of Things (IoT) technology as the country moves forward with the adoption of Industrial Revolution 4.0. As a result, a novel approach based on spatial and thermal analysis is proposed and presented, along with a low-cost thermal and photogrammetric modelling workflow. As a result, the purpose of this project is to monitor durian orchards using drones equipped with thermal and red-green-blue (RGB) digital cameras. Thermal maps are presented to demonstrate the relationship between vegetation and soil temperature, and digital imagery from an early stage of preparation in the orchard is analysed for overall management system improvement. The findings indicate that the uneven ground surface of the orchard may have an effect on the irrigation system and crop yield production. Thermal imaging also reveals variations in soil temperature that are related to soil humidity. A well-managed orchard is essential for ensuring that the crop grows in a healthy state. The data acquisition and processing part of this workflow are being tested in Alor Gajah Smart Durian Orchard Management Project, Melaka, Malaysia.